Trends in consumption of packed processed foods in India: Insights and implications - Suresh, A.; Rajes, I.D.; Veettil, Prakashan Chellattan (TAFSSA, 2024)
This research note provides a comprehensive analysis of consumer behaviour, food consumption, and dietary patterns concerning packaged and processed foods in India over the past decade. The growing availability and consumption of processed and packaged foods have brought significant changes to traditional dietary habits, influencing not only the types of foods consumed but also their frequency and nutritional impact. This note aims to highlight how these foods influence dietary trends, explore the implications of this growing phenomenon, and offer insights to address emerging challenges. The study is based on data from the 2022–2023 National Sample Survey Office (NSSO) consumer spending survey, which captures the latest trends in food consumption. This data is compared with findings from the 2011–2012 NSSO survey round to highlight changes over time, offering a decade-long perspective on the evolution of dietary habits in India.